1995
DOI: 10.1104/pp.109.4.1167
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Binding Activity of Pea Lectin Expressed in White Clover Hairy Roots

Abstract: Dénarié et al., 1992). Nodulation is regulated by a two-way exchange of plant and bacterial signal molecules (Fisher and Long, 1992;Spaink et al., 1993). Signal exchange begins in the rhizosphere. Rhizobia sense flavonoids secreted by seeds and by the host plant root, which activate the constitutively expressed nodD gene product (reviewed by Schlaman et al., 1992). This step is a determinant of host plant specificity in some Rhizobium-host plant combinations (Horvath et al., 1987; Spaink et al., 1987). Transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 40 publications
(71 reference statements)
2
23
0
1
Order By: Relevance
“…This is consistent with the prediction (41) that the glucomannan is required for lectin-mediated attachment to root hairs. At alkaline pH, the root lectin which binds the glucomannan is released from the root hairs, and this probably prevents glucomannan-mediated attachment (16,41). An alternative mechanism of attachment has been proposed to occur at alkaline pH, a mechanism mediated via bacterially made rhicadhesin (56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the prediction (41) that the glucomannan is required for lectin-mediated attachment to root hairs. At alkaline pH, the root lectin which binds the glucomannan is released from the root hairs, and this probably prevents glucomannan-mediated attachment (16,41). An alternative mechanism of attachment has been proposed to occur at alkaline pH, a mechanism mediated via bacterially made rhicadhesin (56).…”
Section: Resultsmentioning
confidence: 99%
“…Under slightly alkaline conditions the lectin is released from pea root hairs, significantly reducing this type of attachment (16). However, rhicadhesin, a calcium-binding protein produced by all tested members of the Rhizobiaceae (56), can facilitate attachment to root hairs under neutral or alkaline conditions (41).…”
mentioning
confidence: 99%
“…It has been reported that carbohydrates in glycoproteins are important for protein folding (12,13,17), stability (11,18), macromolecular interactions, and activity (19)(20)(21). Furthermore, alteration of glycosylation can affect the immunogenicity of therapeutic proteins as it has been demonstrated in the case of interferon beta (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…These lectins localize to root hair tips and are thought to help convey host-symbiont specificity by binding simultaneously to the plant cell wall and to saccharide moieties on the surfaces of compatible bacteria (41,43,79). A series of experiments in which a variety of transgenic plants expressed lectins from other species of legumes has shown that the presence of heterologous lectins often allows transgenic plants to respond to symbionts that are usually noncompatible, provided that the heterologous lectin can bind to the noncompatible bacteria and provided that the noncompatible bacteria make the proper Nod factor (42,79,171,172).…”
Section: Adhesion Of Rhizobia To Root Hairsmentioning
confidence: 99%